A new tool for environmental regulation? The connection between environmental administrative talk policy and the market disciplinary effect. (1st December 2020) - Wang, Jiayi; Lei, Ping
Abstract: Environmental administrative talk is a comprehensive interactive policy network that involves multiple parities. The information on local governments' environmental performance is disclosed, disseminated to the public and market through the media in the process. In this paper, we analyse how this policy influences environmental governance through the stock market. By adopting the event study methodology, we estimate the short and long-term policy effects of environmental administrative talk. The results show that there are negative and enduring abnormal returns after such "talk". These findings indicate that environmental administrative talk triggers a market disciplinary effect, which can work as a new tool for environmental governance. Our paper enriches mechanism research on environmental administrative talk and further confirms the deterrence effect in environmental governance. Moreover, we provide a perspective to tackle environmental problems from the bottom up by utilizing the strength of the public and market regarding policy planning and analysis.